SHOPPING ORIENTATION AND ONLINE TRUST TO ENHANCE ONLINE PURCHASE INTENTIONS WITH GENDER DIFFERENCES AS MODERATOR - Nur Ika Effendi; Rizki Maulana Akbar; Yanti Murni (Journal of Economics, Business, and Government Challenges, 2021)
The use of the internet now seems to have become a primary need. The growth of e-commerce in Indonesia is driving the popularity of non-cash transactions. The purpose of this study, first to give an overview and the implications of the influence of shopping orientation and trust in online consumer purchase intentions. Second, see gender differences as moderating variables because in the virtual group by gender plays a role in communication and e-commerce transactions. Purposive random sampling and Proportional Random Sampling used in sampling techniques. Regression Modeling of Moderating Variable with a Method of Sub Group used in this study with the analysis tool is SPSS 25. Suggestions that can be recommended for online shopping providers the expected to need a strategy in increasing trends in shopping at home by providing complete information. Also, consumer confidence in the services is crucial with the suitability of goods sold with completed information.